2022
DOI: 10.1371/journal.pbio.3001634
|View full text |Cite
|
Sign up to set email alerts
|

Temporal analysis of melanogenesis identifies fatty acid metabolism as key skin pigment regulator

Abstract: Therapeutic methods to modulate skin pigmentation has important implications for skin cancer prevention and for treating cutaneous hyperpigmentary conditions. Towards defining new potential targets, we followed temporal dynamics of melanogenesis using a cell-autonomous pigmentation model. Our study elucidates 3 dominant phases of synchronized metabolic and transcriptional reprogramming. The melanogenic trigger is associated with high MITF levels along with rapid uptake of glucose. The transition to pigmented s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Across melanoma cell lines and primary patient melanomas, we found that acquisition of melanocytic identity corresponds with enhanced fatty acid uptake and oxidation. Interestingly, a recent study found that the process of melanogenesis relies on elevated fatty acid oxidation in melanocytes and mouse B16 melanoma cells 56 . Our data support the idea that melanocytic identity and dependence on lipid metabolism are intrinsically coupled.…”
Section: Discussionmentioning
confidence: 99%
“…Across melanoma cell lines and primary patient melanomas, we found that acquisition of melanocytic identity corresponds with enhanced fatty acid uptake and oxidation. Interestingly, a recent study found that the process of melanogenesis relies on elevated fatty acid oxidation in melanocytes and mouse B16 melanoma cells 56 . Our data support the idea that melanocytic identity and dependence on lipid metabolism are intrinsically coupled.…”
Section: Discussionmentioning
confidence: 99%
“…We have established a B16 (mouse melanoma cell line)-based LD culturing–induced pigmentation model ( 9 ). This model closely recapitulates the melanogenic pathways and signaling cascades operating in primary human melanocytes ( 9 , 24 , 25 ). The LD-pigmentation model leads to a gradual increase in pigmentation over a 7-day period wherein the day-zero (D0) cells are depigmented; by day four (D4), the pigmentation machinery becomes activated and cells become completely pigmented by day seven (D7) ( Fig.…”
Section: Resultsmentioning
confidence: 87%
“…During LD pigmentation, non-pigmented B16 cells are seeded at a density of 100 cells/cm 2 and over a period of 6-8 days these cells become highly pigmented (Motiani, Tanwar et al, 2018;Natarajan, Ganju et al, 2014b) (Figure 1A). The LD pigmentation model closely recapitulates human melanogenic pathways (Motiani et al, 2018;Natarajan et al, 2014b;Sultan, Basu et al, 2022;Tanwar, Sharma et al, 2022b). We quantitated the increase in the melanogenesis during LD pigmentation model by performing melanin content assay, which showed a gradual increase in melanin synthesis from LD day 0 (D0) to LD day 4 (D4), LD day 5 (D5) and LD day 6 (D6) (Figure 1B).…”
Section: Resultsmentioning
confidence: 89%